(untitled) (Scientific journal of the Fergana State University, 2023)
The world has the same faces, the same streets, the same tones a lot. These similarities can be seen in the world of literature. Similar names, similar plots and similar experiences, etc.… But their style of expression, the impression they leave on the reader is different. Today we are going to talk about similar experiences on a similar topic. This article discusses the theme of a mother and the image of a mother depicted in stories with a smilar plot. Both stories focus on the similsrities and differences of the mother image.